Treatment patterns of anti‐tumour necrosis factor‐alpha and prognosis of paediatric and adult‐onset inflammatory bowel disease in Korea: a nationwide population‐based study. Issue 6 (6th July 2022) - Choe, Young June; Han, Kyoungdo; Shim, Jung Ok
Summary: Background: The global prevalence of inflammatory bowel disease (IBD) is increasing. However, population‐level data are scarce for Asian populations. Aims: To outline and compare paediatric and adult IBD incidence and prevalence data in Korea, describe prescription patterns, and analyse outcomes of anti‐tumour necrosis factor (anti‐TNF) use in a nationally representative cohort Methods: IBD was identified based on the presence of Rare and Intractable Disease diagnosis codes for Crohn's disease (CD) and ulcerative colitis (UC). We calculated age‐based prevalence and incidence, and examined prescription patterns. We used a Cox proportional hazard model to calculate the hazard ratio (HR) for undergoing surgery. Results: The prevalence of CD increased between 2006 and 2015, particularly among those aged 10–19 years (12.7–35.5 patients per 100, 000 people). The use of anti‐TNF agents increased from 3.2% to 22.9% in paediatric CD patients. Early use of an anti‐TNF agent increased 25‐fold in CD patients. Further, CD patients aged 0–14 years were most likely to undergo fistulectomy (HR, 2.63; 95% confidence interval [CI], 1.73–3.97). Children with UC had a higher risk of undergoing surgery (HR, 3.01; 95% CI, 1.33–6.83) than adults. Early use of an anti‐TNF agent in CD patients was associated with lower odds of surgery than late‐stage use. Conclusion: The prevalence of IBD has increased over time, especially among paediatric patients. Given the magnitude of paediatric IBD disease burden, a multi‐faceted approach is needed for early detection and vigilant monitoring to aim for better prognosis. Abstract : The global prevalence of inflammatory bowel disease (IBD) is increasing; however, population‐level data is scarce for Asian populations. In South Korea, the prevalence of CD increased between 2006–2015, particularly in teenagers aged 10–19 years (12.7 to 35.5 patients per 100, 000 people), and the use of anti‐TNF agents increased from 3.2% to 22.9% in pediatric CD patients. Given the magnitude of pediatric IBD disease burden, a multifaceted approach is needed for early detection and vigilant monitoring to aim for a better prognosis.